ANALISIS KANDUNGAN MERKURI (HG) DI DALAM TUBUH IKAN PATIN SIAM (Pangasius hypopthalmus) YANG DIBERI PERLAKUAN FITOREMEDIASI DENGAN TANAMAN AZOLLA (Azolla microphilla) - Safratilofa Safratilofa; Kaizar Kaizar (Universitas Batangahari Jambi, 2018)
In 2014 the Batanghari River has been polluted with severe polluted category entering into class D group by Jambi Provincial Environment Agency 2014 with effluent content of 0.3265 ppm. One of the contaminants is mercury (Hg). This is due to increased mining, industrial and agricultural activities along the Batanghari River. Batanghari River is a source of water for Sipin Lake. Sipin Lake has much to do with fish farming in KJA for catfish. The potential of Hg content in the waters has exceeded the standard quality standard that can thwart the fish farming activities. Therefore, research to find solutions to solve the contamination of mercury (Hg) content in catfish (Pangasionodon hypopthalmus) with technical use of azolla (Azolla microphilla) as phytoremediation to prevent Hg from entering fish body. This Research conducted around KJA fish cultivation in the waters of Sipin Lake Jambi. The design of this research is Completely Randomized Design with azolla density level as treatment. The results of analysis and observation showed that the density of azolla gave no significant effect on the content of mercury (Hg) in water and fish meatKeyword: phytoremediation, markuri, sipin lake, Azolla microphilla, Pangasionodon hypopthalmus